Comparative and Legal Analysis of the Labor-Legal Status of a Higher School Teacher - LUKINOVA, Svetlana Alekseevna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The article analyzes the development trend of social and labor status of a higher school teacher, due to the processes of globalization and modernization of educational systems of the states that emerged after the collapse of the Soviet Union. The author substantiates the relevance of the use of comparative legal method in the study of the problems connected with the formation and fixation of social and labor rights and guarantees to a high school teacher in Russia and the Republic of South Ossetia. The modern problems of the labour-legal status of high school teachers in Russia and the Republic of South Ossetia are designated in this article. The author uses the method of comparative jurisprudence while analyzing the regulation of salary of a higher school teacher in Russia, Republic of South Ossetia and other countries. The article highlights the normative legal acts in accordance with which the modernization of higher educational systems in the Russian Federation and the Republic of South Ossetia takes place. Finally, there have been made conclusions and generalizations aimed at improving of the legal regulation of social and labor status of a higher school teacher in Russia and the Republic of South Ossetia.